Pelatihan Pengolahan Pupuk Organik Cair Dari Limbah Sayur di Desa Ngampel Wetan Kabupaten Kendal : Training on Processing Liquid Organic Fertilizer from Vegetable Waste in Ngampel Wetan Village, Kendal Regency - Fajar, Dimas Rizqi; Prasasti, Anggun Niken; Afiqoh, Fadhila Aulia Nur; Respati, Iklima Nur; Sari, Betty Fitria Nita; Prastyo, Irman Said (Lembaga Pengembangan Kinerja Dosen, 2024)
Training on processing liquid organic fertilizer from vegetable waste in Ngampel Wetan Village, Kendal, was conducted to increase community awareness and skills in utilizing household waste, especially vegetable waste, as a basic ingredient for making liquid organic fertilizer. This activity was motivated by the community's dependence on inorganic fertilizers in agriculture, so the potential of liquid organic fertilizer can be applied to farmers in Ngampel Wetan Village. With this training, the community is expected to be able to reduce dependence on chemical fertilizers by switching to organic fertilizers that are safer and more economical. The method used in processing vegetable waste as liquid organic fertilizer, observation, theory, product targets, implementation, and evaluation aims to solve problems in Ngampel Wetan Village, Ngampel District, Kendal Regency. It is hoped that with this training, the community of Ngampel Wetan Village can utilize vegetable waste into liquid organic fertilizer and utilize it in agricultural activities so that liquid organic fertilizer can overcome the problems of waste and limited fertilizer. Pelatihan pengolahan pupuk organik cair dari limbah sayur di Desa Ngampel Wetan, Kendal, dilakukan guna meningkatkan kesadaran dan keterampilan masyarakat dalam memanfaatkan limbah rumah tangga, khususnya limbah sayur, sebagai bahan dasar pembuatan pupuk organik cair. Kegiatan ini dilater belakangi oleh ketergantungan masyarakat terhadap penggunaan pupuk anorganik dalam bidang pertanian, maka potensi pupuk organik cair dapat diaplikasikan ke para petani di Desa Ngampel Wetan. Pelatihan pupuk organik cair kepada masyarakat diharapkan bisa mengurangi ketergantungan pada pupuk kimia dengan beralih ke pupuk organik yang lebih aman dan ekonomis. Metode yang digunakan pengolahan limbah sayur sebagai pupuk organik cair yaitu observasi lapangan, teori, sasaran produk, pelaksanaan, dan evaluasi bertujuan untuk memberikan solusi atas permasalahan di Desa Ngampel Wetan Kecamatan Ngampel Kabupaten Kendal. Diharapkan, dengan adanya pelatihan ini, masyarakat Desa Ngampel Wetan dapat memanfaatkan limbah sayuran menjadi pupuk organik cair dan memanfaatkannya dalam kegiatan pertanian, sehingga pupuk organic cair dapat mengatasi permasalahan sampah dan keterbatasan pupuk